Conversion of immunohistochemical markers and breast density are associated with pathological response and prognosis in very young breast cancer patients who fail to achieve a pathological complete response after neoadjuvant chemotherapy - Zhao Y; Wang X; Huang Y; Zhou X; Zhang D (Cancer Management and Research, 2019)
Yue Zhao,1 Xiaolei Wang,2 Yuanxi Huang,1 Xianli Zhou,2 Dongwei Zhang31Department of Breast Surgery, The Tumor Affiliated Hospital of Harbin Medical University, Harbin, People’s Republic of China; 2Department of In-Patient Ultrasound, The Second Affiliated Hospital of Harbin Medical University, Harbin, People’s Republic of China; 3Department of Surgery, The Second Affiliated Hospital of Harbin Medical University, Harbin, People’s Republic of ChinaPurpose: Patients younger than age 35 that fail to achieve a pathologic complete response (pCR) after Neoadjuvant chemotherapy (NACT) tend to have worse long term outcomes. The purpose of our study was to assess the correlation between the conversion of immunohistochemical (IHC) markers and breast density and investigate their association with pathological response and prognosis.Methods: We included 119 patients younger than age 35 who failed to achieve a pCR after NACT in this analysis. We evaluated the clinical and pathological response to NACT by the Union for International Cancer control (UICC) and the Miller-Payne grading (MPG) systems, respectively. A breast density assessment was applied via mammography examination at the time of diagnosis. MPG and breast density (BD) have been combined to define a specific classification of three risk levels to evaluate the prognosis of these patients.Results: The diameter changes of the tumors and lymph nodes were negatively associated with hormone receptor conversion and positively correlated with Ki67 conversion. A significantly large size change was observed in the groups demonstrating conversion from HER-2 (+) to (−). The variation level of IHC markers was related to MPG and BD and was associated with the survival rate of the patients. Patients with a high breast density and low Miller-Payne grading after NACT had a higher risk of distant metastases or local recurrences.Conclusion: ER, PR and Ki67 conversion are closely related to MPG, while PR and Ki67 conversion are closely related to BD. While ER and PR conversion are independent and significant predictors of disease free survival (DFS) and overall survival (OS), HER-2 and Ki67 conversion are only significant for DFS. This risk factor grouping provides a useful index to evaluate the risk of young women with breast cancer who fail to achieve a pCR.Keywords: young breast cancer, neoadjuvant chemotherapy, IHC markers, conversion, breast density, survival